2023
DOI: 10.1111/1755-0998.13851
|View full text |Cite
|
Sign up to set email alerts
|

Comparing iDNA from mosquitoes and flies to survey mammals in a semi‐controlled Neotropical area

Abstract: Ingested‐derived DNA (iDNA) from insects represents a powerful tool for assessing vertebrate diversity because insects are easy to sample, have a diverse diet and are widely distributed. Because of these advantages, the use of iDNA for detecting mammals has gained increasing attention. Here we aimed to compare the effectiveness of mosquitoes and flies to detect mammals with a small sampling effort in a semi‐controlled area, a zoo that houses native and non‐native species. We compared mosquitoes and flies regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…In addition, while the 16SrRNA mini-barcode was more effective for mammal species detection, the total species number increased by using the 12SrRNA barcode (Figure 2). Similar trends were also reported when both primer pairs were used to amplify iDNA obtained from mosquitoes and carrion flies (Saranholi et al, 2023),…”
Section: Ta B L E 1 (Continued)supporting
confidence: 79%
See 3 more Smart Citations
“…In addition, while the 16SrRNA mini-barcode was more effective for mammal species detection, the total species number increased by using the 12SrRNA barcode (Figure 2). Similar trends were also reported when both primer pairs were used to amplify iDNA obtained from mosquitoes and carrion flies (Saranholi et al, 2023),…”
Section: Ta B L E 1 (Continued)supporting
confidence: 79%
“…Although Saranholi et al (2023) reported higher mean values in mosquitoes (3.6 ± 4.3 OTUs) and carrion flies (saprophagous flies:…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 93%
See 2 more Smart Citations
“…The diversity of bloodmeal origins captured across a number of mosquito species, con rms that mosquitoes are a powerful, emerging tool for characterising vertebrate diversity. The technique has potential application to a range of ecological and conservation issues, such as monitoring rare or endangered species 44 , and measuring biodiversity 45,46 . It can also be used to understand host feeding patterns, which is a crucial component for assessing the risk of pathogen transmission pathways and human spillover.…”
Section: Discussionmentioning
confidence: 99%